Characterization and distribution of potentially avian pathogenic eschericia coli isolates from broilers in Peru - Carranza, Claudia (2012)
Avian colibacillosis produced by Escherichia coli infections cause high mortality and morbidity in poultry farms. The objective of this study was to identify the pathogenic isolates of Peruvian broiler farms based in the presence of five genes encoding the virulence factors: iss, iucC, tsh, cvaC and irp2 by the Multiplex PCR. A total of 36 chicks between 14 and 31 days old from three poultry farms located in the north, centre, and south of Peru were sampled. Three colonies suspected to be E. coli were isolated from the intestine of each bird (n=108 colonies), and were biochemically tested with TSI, SIM, LIA, CITRATE and EMB mediums for the confirmation of the diagnostic. The 41 positive colonies to E. coli were analysed by Multiplex PCR, resulting 65.95% potentially pathogenic (carriers of two or more virulence genes); moreover, 9.8% of the isolates had all five genes. Three pathotypes containing irp2, iucC and tsh genes were found in La Libertad and Lima area.